Organochlorine pesticides in fat tissue of cetaceans at the Crimean coast of the Black Sea - T. O. Barabashin; I. V. Suvorova; I. V. Korablina; S. N. Kulba; A. V. Korosteleva; А. N. Postnikova (Известия ТИНРО, 2024)
Accumulation of persistent organochlorine pesticides (OCP) in fat tissue was examined for the mammals found released ashore along the Crimean coast of the Black Sea in 2018–2022. This group of animals is positioned at the top of food chain in the local marine ecosystem. Statistically significant dependence of the accumulation on sex (males are more contaminated than females) and age (adults and juveniles are more contaminated than calves and neonates) is found. Besides, the pesticides concentration in fat from dorsal tissue is generally higher than in fat from caudal stem, but the difference is not significant. In the tissue of harbor porpoises and common dolphins, the mean OCP concentration decreased in the order: p,p′-DDE > β-HCH > p,p′-DDD > p,p′-DDT, whereas bottlenose dolphins had the order: p,p′-DDE > p,p′-DDD > β-HCH > p,p′-DDT. The most common metabolites were DDE, and their accumulation was the highest. The concentration of DDD was considerably lower, and significant accumulation of DDT was observed rarely, so the mean concentration of these group of metabolites was the lowest.